2020
DOI: 10.3390/met10040480
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Tensile Properties of Diffusion Bonded Austenitic Fe-Base Alloys—Before and After Exposure to High Temperature Supercritical-CO2

Abstract: Austenitic Fe-base alloys, SS 316H and Alloy 800HT, were diffusion bonded for use in compact-type heat exchangers in supercritical-carbon dioxide (S-CO2) Brayton cycles. For diffusion bonded 316H, grain boundary migration across the bond-line was observed despite the formation of some Cr-rich carbide, and its tensile properties were similar to those of as-received 316H. However, diffusion bonded Alloy 800HT exhibited severely degraded elongation compared to as-received 800HT due to the formation of continuous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…This explains why the strengthening effect increases with increasing temperature. Furthermore, some studies [29,65,125,126] have reported that the mechanical performance of base materials or welded samples or diffusion-bonded joints of austenitic steel 316SS and 800HT were greatly compromised after exposure to high temperature S-CO 2 . The fracture mode gradually changed from transgranular fracture to intergranular fracture at room temperature due to the carburization in high temperature S-CO 2 .…”
Section: Stress Corrosion 41 Effects Of Corrosion On Mechanical Behaviormentioning
confidence: 99%
“…This explains why the strengthening effect increases with increasing temperature. Furthermore, some studies [29,65,125,126] have reported that the mechanical performance of base materials or welded samples or diffusion-bonded joints of austenitic steel 316SS and 800HT were greatly compromised after exposure to high temperature S-CO 2 . The fracture mode gradually changed from transgranular fracture to intergranular fracture at room temperature due to the carburization in high temperature S-CO 2 .…”
Section: Stress Corrosion 41 Effects Of Corrosion On Mechanical Behaviormentioning
confidence: 99%
“…Supercritical carbon dioxide (SCO 2 ) is considered as one of the prime coolant candidates for next-generation power plants, as it has advantages of higher efficiency, smaller component sizes, fewer components, and a simpler cycle layout, etc. [1,2]. In the SCO 2 Brayton cycle system, material selection of the key components such as heat exchangers and pipes is one of the important problems of long-term, safe operation [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Oleksak et al [16] further suggested that O 2 , H 2 O, and SO 2 had negligible effects on the oxidation of ferritic Fe alloys, while SO 2 could significantly enhance the rate of oxidation for austenitic Fe alloys. Fourthly, studies have examined the integrity of welding joints, including examinations of the diffusion-bonded technique [17] towards the printed circuit heat exchanger (PCHE) [1,18], the fusion-weld technique [2], and the typical gas tungsten arc welding (GTAW) technique [19]. Fifthly, studies have examined the preparation of the coating on the metal substrate, such as the deposition of a Cu coating [20], a Si coating [21], an Al coating [22,23], a Cr coating [24,25], and a NiAl coating [26].…”
Section: Introductionmentioning
confidence: 99%